Contextualization of Zhihar Based on Tafsir Literature In the Communication Relationship between Husband and Wife - Eka Putri, Nerisma (Maqasid: Jurnal Studi Hukum Islam, 2024)
Abstract: In marriage, Allah swt legalizes the relationship between husband and wife, with the husband having to keep good words in order to avoid words that hurt his wife. Especially if the husband utters zhihar to his wife. In the Jahiliyyah era, zhihar was considered a divorce, then Islam canceled it with the rule that the husband was prohibited from mixing with his wife before paying expiation. The origin of the terminology of zhihar was due to the issue of a woman named Khaulah bint Tsa´labah who had been zhihar by her husband Aus ibn Shamit, Aus said to his wife: "You are to me like my mother's back" with the intention that he should no longer have sex with his wife. For this reason, researchers are interested in examining the contextualization of zhihar in husband and wife communication relations based on the perspective of tafsir literature in the current era. This research uses library research with a qualitative approach, to examine the phenomenon of zhihar on the communication relationship between husband and wife based on contemporary tafsir literature. So that the results found that zhihar in terms of context, there are differences between Jahiliyah and contemporary times, that in the Jahiliyah era, zhihar was used as a form of insult to wives who could not serve them until they finally fell divorce, while in the contemporary era zhihar is interpreted as a form of respect in beauty. Husbands communicate using figures of speech without explicit intent, giving birth to different meanings. However, even if the communication is conveyed in jest, it is still legally imposed as ẓhihar.   Keywords: Contextualization of Zhihar, Contemporary Tafsir Literature, Communication Relations.